Private equity challenge - fluidra sa - valuation - Lucas, Pedro Ruiz Callé (2021)
This Investment Committee Paper was elaborated by a group of students from the Master’s in Finance Program at Nova School of Business and Economics which is intended to be used for academic purposes only. It consists of an investment proposal for a leveraged buy out on Fluidra SA, a global leader in the Pooland Wellness industry, with a robust international presence and an extensive portfolio. Operating in both new build and after market sub-sectors, providing high quality swimming pool equipment that ranges from above-ground and in-ground pools to a complete line of accessories and chemical products. The groups ought to define the optimal value creation and business model for the proposed leveraged buy out, based on an extensive market and company analysis, also studying the company’s valuation methodologies. In addition, the group proposed an optimal capital structure and selected exit strategies.